The Influence Of Buy-Now, Pay-Later Schemes, Social Media, And Peer Pressure On Impulsive Buying (Case Study In E-Commerce Consumers In Jabodetabek) - Mohamad Agil Qorizqi Ghaniyo; Astrid Dita Meirina Hakim (Jurnal Ilmiah Multidisiplin, 2025)
This research aims to examine the influence of social media, peer pressure, and Buy Now Pay Later (BNPL) services on impulsive buying behavior among Indonesian e-commerce consumers. A total of 176 Generation Z respondents from Greater Jakarta (Jakarta, Bogor, Depok, Tangerang, Bekasi) were selected using purposive sampling. The study employed a quantitative approach with a structured Likert-scale questionnaire, and data were analyzed using IBM SPSS version 22.0. Several statistical tests, including validity, reliability, classical assumption, and multiple regression analysis, were conducted. The results indicate that social media influence and peer pressure have a significant positive effect on impulsive buying behavior, whereas BNPL does not show a statistically significant impact. These findings highlight the stronger role of social environment and digital exposure in shaping consumer impulsiveness compared to deferred payment methods. The study provides insights for marketers, policymakers, and financial service providers on managing consumer behavior in the digital commerce landscape.